A DISCOURSE ON THE CONSCIOUSNESS OF ETHICS AMONG THE MALAYS IN MALAYSIA: 1970 TO 2000 - KHALID ALI, KHALIDAH (2019)
Malaysia, a high middle-income nation has charted commendable economic progress since her 1957 independence and undergone a successful economic transformation to realize Vision 2020 and Transformasi Nasional 2050 aspirations (to be a developed nation). However, changes in societal values and norms may pose a challenge to achieving her developed status.